链传动中纵向振动问题的研究 - 程岩; 李宝林; 张燕; 齐帅; 史新国 (Jixie Chuandong, 2012)
By using the theory of vibration on multi-degree of freedom,the longitudinal vibration of roller chain is studied.Based on the model of dynamics for longitudinal vibration of roller chain,the equations of longitudinal vibration for roller chain are derived and the formulas for computing the natural frequency and method for computing the natural mode are given.Some measures to avoid resonance of roller chain in chain drives are presented.